A Matemática e o consumo consciente de água na escola: Formulação e resolução de problemas no contexto do Projeto Agente Jovem - Pereira, Wellton Cardoso (2018)
This work was developed within the scope of the ProEMI-Innovative Hicg School Program and in the context of the Young Agent and Conscious Consumption of Water Project at the Santa Tereza High School in Altaneira, Ceará. It aimed to develop and evaluate a proposal of Basic Mathematics teaching from the identification, formulation and solving problems. We developed an action research with qualitative analysis centered on the school context and the emerging problems of this context. The theoretical framework adopted in this research involved the following topics: High School in Brazil, Formulation, Problem Solving, Teaching-Learning Methodology-Assessment through Problem Solving, Contextualization, Innovative High School Program - ProEMI, Young Agent Project and Conscious Water Consumption. The research developed a proposal of Basic Mathematics teaching in five Modules, with 8 Young Agents and 8 Students Mobilized of said school. The results of the 16 activities carried out from March to September 2017 were evaluated. The results showed that the proposal contributed to the training of students, giving them the opportunity to develop personal and professional skills and to improve the ability to formulate and solve problems. In addition, it favored community awareness in combating waste of water at school, and collective work is a relevant practice in this process. It is worth noting that, at the end of the research, Young Agents and Mobilized Students revealed the change in behavior in relation to water consumption and found improvement in Basic Mathematics learning. From the development of the formulation and problem solving, such as activities of the teac hing proposal, we could conclude that this methodology helps to understand the teaching of Mathematics when the pedagogical process starts from the identification of real problems by the students.